Somatic features and body posture in children with scoliosis and scoliotic posture - Wilczyński, Jacek; Lipińska Stańczak, Magdalena; Dworakowska, D; Wilczyński, Igor (Journal of Education, Health and Sport, 2017)
Abstract The aim of the study was to evaluate the relationship between somatic features and body posture in children with scoliosis and scoliotic posture. The study included 28 girls aged 7-18 with scoliosis and scoliotic posture. The selection of the subjects was deliberate. Height measurements were conducted with an anthropometer and weight measurements were done with an electronic scale. Body posture tests were performed using Exhibeon 3D digital photogrammetry and digital radiographs. The significant Spearman correlations between postural variables for the sagittal plane and the somatic variables regarded: trunk inclination angle and BMI (R= 0,4553, p= p=0,015), Abs of the trunk inclination angle and BMI (R = 0.5522, p = 0.002), length of thoracic kyphosis and BMI (R=0,4147, p=0.028), lumbar lordosis and BMI (R=0,4509, p=0,016). The significant Spearman correlations between scoliotic posture variables and the somatic variables concerned: length of primary lordosis and body height (R =0,4923, p=0.008), the length of the primary lordosis and body mass (R = 0.3932, p = 0.038), the length of the primary lordosis and BMI (R=0,4923, p=0.008). Variation analysis regarding postural (Exhibeon) and somatic variables showed significant correlations between the direction of the primary curvature and body mass (p=0,0432), body height and primary angle location (p=0,0290) and between the height of the body and the location of the secondary angle (p = 0,0278).